Analysis of Service Quality Factors of the Regional Planning Agency of Aceh - T. Aznal Zahri; Abdul Rahman Lubis; Muslim A. Djalil; . Syafruddin (Ital Publication, 2023)
Objective: This study examines how collaborative public innovation, transformational leadership, knowledge acquisition, employee competencies, innovative climate, and organizational performance affect service quality at the Regional Planning Agency of Aceh. Methods/Analysis: The study used quantitative analysis, qualitative interviews, and surveys. The data were analyzed using the SERVQUAL model and scatter analysis approaches. The correlation between variables was analyzed by Spearman rho correlation, while Kruskal-Wallis analyzed the significance between variables. Finding: The SERVQUAL model shows the Regional Planning Agency of Aceh provides good quality services; 98% of respondents gave an excellent rating, and 12% were good. Scatter analysis shows that the agency consistently meets expectations. Spearman rho correlation analysis shows that all determinant factor variables have a strong relationship with improving service quality and are also significant between variables (p<0.05). Novelty/Improvement: Improving the quality of the organization (Regional Planning Agency of Aceh) is primarily determined by the knowledge acquisition factor, which is followed by collaborative public innovation, transformational leadership, employee competencies, and an innovative climate. Doi: 10.28991/ESJ-2023-07-05-017 Full Text: PDF